Prevalence, Antibiotic-Resistance, and Growth Profile of Vibrio spp. Isolated From Fish and Shellfish in Subtropical-Arid Area - Abdalla, Tarfa; Al-Rumaithi, Hind; Osaili, Tareq M.; Hasan, Fayeza; Obaid, Reyad S.; Abushelaibi, Aisha; Ayyash, Mutamed M. (Frontiers in Microbiology, 2022)
The study aimed to determine the prevalence of different species of Vibrio spp., in fish and shellfish sold in a subtropical-arid country (United Arab Emirates). It also examined the antimicrobial resistance of the isolated species and their growth behavior upon in vitro environmental changes with respect to temperature, pH, and salinity. The prevalence of Vibrio spp. in fish and shellfish samples was 64.5 and 92%, respectively. However, V. parahemolyticus were detected in a mere 7.5 and 13.0% of the samples, respectively. On the other hand, V. mimicus was detected in 1.5 and 8.5% of the samples, respectively. None of the six antibiotics studied except for Sulfamethoxazole-trimethoprim were effective against fish Vibrio spp. isolates. On a similar note, three antibiotics namely Penicillin, Daptomycin, and Vancomycin were ineffective against the shellfish isolates. The growth of the microorganisms did not show any significant trend with changes in pH and salinity. The optimum temperature for Vibrio spp. growth was observed to be 37°C.